ChemInform Abstract: Enantioselective Hydrogenation of β, β‐Disubstituted Unsaturated Carboxylic Acids under Base‐Free Conditions. Issue 30 (July 2016) - Yan, Qiaozhi; Kong, Duanyang; Zhao, Wei; Zi, Guofu; Hou, Guohua
Abstract: The additive‐free protocol works also for β, β‐disubstituted unsaturated aldehydes and γ, γ‐disubstituted alcohols.